Geochemistry and origin of Ordovician oils in the Rewapu Block of the Halahatang Oilfield (NW China) - You-Jun Tang (KeAi Communications Co., Ltd., 2018)
Abstract The oils in the Rewapu Block of the Halahatang Oilfield in the Tarim Basin (northwestern China) were geochemically analyzed by gas chromatography–mass spectrometry to investigate their origin and possible secondary alteration. The physical properties and chemical compositions of these Ordovician oils vary greatly, ranging from light to extremely heavy oils. All these oils belong to one single population and were derived from same source kitchen/bed. The differences in their chemical compositions and physical properties mainly result from secondary alteration of oils that were charged during the early phase of trap formation. The thickness of Upper Ordovician and Silurian caprocks of oil reservoirs in the Rewapu Block is higher than that in the north part of the Halahatang region, and therefore, significant biodegradation process is prevented. Compared to heavy oils in the north part, the Rewapu oils are dominated by light oils with no 25-norhopanes and no GC–MS “hump” (UCM: unresolved complex mixture) on the chromatographic baselines. The heavy oils in Wells RP7 and RP101C were primarily influenced by water washing since apparent reduction of alkylated dibenzothiophenes was observed. The local geological background favored the water washing alteration. The reservoir geochemical study has practical application in hydrocarbon exploration and predicts the nature of oils in this oilfield.